CAUGHT IN THE NET. NOTES FROM THE ELECTRONIC UNDERGROUND - Readings, Bill (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
Reflections on the epistemological and institutional shifts in scholarly research and publication that are brought about by electronic technology. Particular attention is paid to the potential crisis in current modes of the legitimation of knowledge and scholarly practices.